Filipino friends - Romulo, Liana; Dandan-Albano, Corazon (Tokyo: Tuttle Publishing, 2007)
From the author of Filipino Children's Favorite Stories comes a book for young children that features a Filipino-American boy visiting the Philippines for the very first time. Each watercolor illustration is labeled with English words and their Filipino translations and shows readers both the similarities and differences between Western and Philippine lifestyles. Filipino Friends, perfect for Filipino-American's or those just interested in the culture, is indispensable in bridging the gap between the two cultures.
Keywords: Philippines. -- Juvenile literature